A Computer Supported Interprofessional Education Initiative: Using Technology to Advance Interprofessionalism - Kellie Smith; Reena Antony; Sokha Koeuth; Lauren Collins; Anthony Frisby (Association of American Medical Colleges, 2013)
Abstract Introduction A long-term strategic goal of Thomas Jefferson University's InterProfessional Education Center (JCIPE) was identified to "create innovative learning environments that support interprofessional education including state-of-the-art technologies." In actualizing this goal, Jefferson's interprofessional education (IPE) curriculum, the Health Mentor Program (HMP), was enhanced with computer-supported collaborative learning techniques to assist student teams with group processing, team building, and reflection. Combining traditional IPE activities with technology-supported components incorporates advantages of both delivery methods. This mixed methodology combines rewarding face-to-face interactions while also providing increased flexibility, reflection, and depth of discussion that the online environment affords. Methods The Jefferson HMP is a 2-year interprofessional learning experience for nursing, medical, pharmacy, occupational, physical, and couples and family therapy students in which teams of students are paired with a person who has one or more chronic illnesses (i.e., a health 'mentor'). Over the course of the program, teams of students visit a person with a chronic disease or impairment while completing a series of module team assignments. As part of these modules, student teams complete comprehensive life and health histories; assess wellness; develop home and medication safety plans; and create individualized action plans for their health mentors to promote healthy behaviors using computer technology tools such as wiki sites, asynchronous discussion boards and online surveys. Results Most students expressed satisfaction with the online discussion board format. Students generally reported satisfaction with the accessing and using the asynchronous discussion board. Course evaluation demonstrated that the wiki was easy to use and facilitated team communication; in fact, 73% to 91% of students from all six health professions agreed it was user friendly and allowed for team and individual contribution. Discussion With 2 years of experience leading online discussion boards, we have found that it is best if the program is optional for both student teams and faculty. We now present this option at the orientation of the IPE program and allow student teams to decide together whether they prefer this format or would prefer to debrief face to face. Additionally, some faculty prefer to facilitate online discussion boards given hectic and already full teaching schedules; by working online, this allows them to lead an IPE discussion when they might not otherwise have time in their daily schedules to facilitate in-person sessions.